WAVE-CURRENT INTERACTION ON OFFSHORE SPAR PLATFROMS IN MALAYSIA WATER - TUHAIJAN, SITI NOR ADHA (2013)
It is well known that in offshore region, wave and current coexist simultaneously that make them being the most important processes controlling the hydrodynamic behavior. The presence of current in the water body gives a significant effect to the response of the offshore structure. Many studies had been done in order to determine the behavior of the wave with the presence of the current. The studies have shown that the wave-current interaction changes the wave behavior and characteristics such as the wave length, wave forces, and slow drift motions. These changes give a significant effect to the response ofthe structure.